PENERAPAN PEMBELAJARAN BERBASIS PENGALAMAN DI LPTK BAGI PENYIAPAN GURU PROFESIONAL - Anik Ghufron (MAJALAH ILMIAH PEMBELAJARAN, 2007)
According to "Undang-undang nomor 14 tahun 2005 tentangGuru dan Dosen ", teacher college institution (LPTK) has astrategic role in preparing professional teachers with fourcompetencies: pedagogical, personal, professional, and socialcompetencies. In this context, LPTK is requested as a goodeducational institution to prepare professional teachers.To anticipate that challenge, LPTK needs to do some programsto prepare professional teachers. One of them is to applyexperience-based instruction because the instruction is therealization of the curriculum design in the classroom.Some activities to support the application of experience-basedinstruction are the synchronization of competency formulation,development of the competency-based field study program, anddevelopment of the performance-based evaluation.